2008
DOI: 10.1111/j.1460-9568.2008.06432.x
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal lobe structures participate differentially in consolidation of safe and aversive taste memories

Abstract: Taste memories are amongst the most important kinds of memories, as adequate identification of safe and toxic edibles will determine the subject's survival. Despite the well-established role that the medial temporal lobe plays in consolidation of memory, specific contributions of the different regions of the temporal lobe to taste memory consolidation remain unknown. In the present report, we assessed the participation of perirhinal cortex (Ph), dorsal hippocampus (Hipp), basolateral (BLA) and central nuclei o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 40 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…The IC is suggested to be important in recognition whether the taste is familiar or novel (Gutiérrez et al, 2003; Bahar et al, 2004b). More recent studies suggested that attenuation of neophobia depends not only on the IC (Rodriguez-Ortiz et al, 2005), but also hippocampus and perirhinal cortex (De la Cruz et al, 2008). …”
Section: Flavor Preferencementioning
confidence: 99%
“…The IC is suggested to be important in recognition whether the taste is familiar or novel (Gutiérrez et al, 2003; Bahar et al, 2004b). More recent studies suggested that attenuation of neophobia depends not only on the IC (Rodriguez-Ortiz et al, 2005), but also hippocampus and perirhinal cortex (De la Cruz et al, 2008). …”
Section: Flavor Preferencementioning
confidence: 99%
“…This is in line with its unique anatomical connections (Figure 1), through which it receives multimodal sensory inputs, including visceral, gustatory, and somatosensory information from sensory thalamic nuclei (Fujita et al, 2010). However, other brain regions, such as the basolateral amygdala (Bla) and dorsal hippocampus, have been shown to be activated during novel taste processing (Yefet et al, 2006; Doron and Rosenblum, 2010), and also to be necessary for safe taste–memory consolidation (De la Cruz et al, 2008). Most of the studies of the molecular mechanisms underlying taste memory were performed in mice and rats, therefore, the present review will focus on these studies.…”
Section: Introductionmentioning
confidence: 99%
“…: Martinez et al ,1981; Davis & Squire, 1984; Dudai, 2002; Kandel, 2001; Alberini, 2008; Gold, 2008; Desgranges et al , 2008; De la Cruz, et al , 2008). Previous results show that intra-amygdala injections of anisomycin impair synaptic plasticity within the amygdala (Huang & Kandel, 2007) and impair fear conditioning (Schafe & Ledoux, 2000; Parsons et al , 2006; Maren et al , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of experiments in which protein synthesis inhibitors injected directly into the amygdala impair memory have generally been interpreted as revealing a role for training-initiated protein synthesis important for the formation of new memories (Duvarci et al , 2005; Nader et al , 2000a,b; Milekic et al , 2007; Cammarota et al , 2004; Izquierdo et al , 2002; Schafe & LeDoux, 2000; Chai et al , 2006), an interpretation common to similar tests of other brain areas as well (Rossato et al , 2007; De la Cruz et al , 2008; Desgranges et al , 2008; Izquierdo et al , 1992; Morris et al , 2006). When trained on fear conditioning tasks in particular, the interpretation is often that protein synthesis is necessary at a primary site of neural plasticity essential for memory formation (Duvarci et al , 2005; Maren et al , 2003; Nader, 2003; Nader et al , 2003a,b); Schafe & LeDoux, 2000), although the evidence for the amygdala as the primary site of memory storage for fear conditioning appears to be unconvincing (Weinberger, 2010).…”
Section: Discussionmentioning
confidence: 99%